The Differential Effect of Excess Aldosterone on Skeletal Muscle Mass by Sex - Kwak, Mi Kyung; Lee, Seung-Eun; Cho, Yoon Young; Suh, Sunghwan; Kim, Beom-Jun; Song, Kee-Ho; Koh, Jung-Min; Kim, Jae Hyeon; Lee, Seung Hun (Frontiers in Endocrinology, 2019)
The effects of excess aldosterone on skeletal muscle in individuals with primary aldosteronism (PA) are unknown. To examine the effects of aldosterone on skeletal muscle mass in patients with PA, by sex, 309 consecutive patients were enrolled. Skeletal muscle and fat mass of 62 patients with PA were compared with those of 247 controls with non-functioning adrenal incidentaloma (NFAI). Body composition parameters were measured using bioelectrical impedance analysis, and plasma aldosterone concentration (PAC) was measured using radioimmunoassay. The PAC in all women, but not in men, showed an inverse association with both appendicular skeletal muscle mass (ASM) (β = −0.197, P = 0.016) and height-adjusted ASM (HA-ASM) (β = −0.207, P = 0.009). HA-ASM in women (but not in men) with PA was 5.0% lower than that in women with NFAI (P = 0.036). Furthermore, women with PA had a lower HA-ASM than 1:1 age- and sex-matched controls with NFAI by 5.7% (P = 0.049) and tended to have a lower HA-ASM than 1:3 age-, sex-, and menopausal status-matched controls without adrenal incidentaloma (AI) by 7.3% (P = 0.053). The odds ratio (OR), per quartile increase in PAC, of low HA-ASM in women was 1.18 [95% confidence interval (CI), 1.01–1.39; P = 0.035]. The odds of HA-ASM in subjects with PA were 10.63-fold (95% CI: 0.83–135.50) higher, with marginal significance (P = 0.069) than in those with NFAI. Skeletal muscle mass in women with PA was lower than that in women with NFAI; suggesting that excess aldosterone has adverse effects on skeletal muscle metabolism.